IDENTIFIKASI ZONA LEMAH BIDANG GELINCIR MENGGUNAKAN METODE SEISMIK REFRAKSI TOMOGRAFI - Hasani, Ruslan; Lepong, Piter (GEOSAINS KUTAI BASIN, 2018)
This research was performed the identifity the lithology of weak zone as a surface of the landslide based on seismic velocity of seismic refraction tomography. The research was conducted on the main road of Tenggarong-Kutai Barat and also on the road of Samarinda-Tenggarong, in Kalimantan Timur. Data acquisition was conducted in one line travel with nine shot point in the same interval. This method used the picking first break of the seismic trace. This travel time as send input data of the Rayfract software of processing of seismic refraction tomography. The processed data shown the image of the seismic velocity of subsurface. The slip surface is interpretated from the boundry of sandstone and clay with velocity of (400 m/s - 1000 m/s) and of (1000 m/s -2500 m/s) respective. The identification on each revealed the types of rock in the study area.